THE INFLUENCE OF DIGITAL LEADERSHIP AND DIGITAL CULTURE ON EMPLOYEE PERFORMANCE AT PT. XYZ SUBANG - Utari, Ayu; Jaya, Umban Adi (International Journal of Multidisciplinary Research and Literature, 2026)
This research is motivated by the digital transformation challenges faced by manufacturing companies, particularly in terms of digital literacy and adaptation to technology-based work systems. The purpose of this study is to determine the influence of Digital Leadership and Digital Culture on Employee Performance at PT. XYZ Subang is a speaker manufacturing company. This study employs a quantitative, descriptive-associative design to examine the relationship between variables systematically. A total of 103 participants were selected as research subjects through purposive sampling, with the main criterion being active involvement in work activities that use digital systems and technology. The data collection tool used a structured questionnaire distributed to all employees of PT. XYZ. The data processing and testing were carried out using multiple linear regression, complemented by testing individual influences with t-tests and joint influences with F-tests. The research findings revealed that digital-based leadership and digital cultural values ​​had a significant impact on employee performance, both when tested separately and simultaneously. These findings emphasize the importance of digitally literate leaders and a technology-adaptive work culture in encouraging employee productivity and work effectiveness in the Industry 4.0 era.